Engineering and Financial Feasibility of Residential Housing Using Greenship Rating Tool Parameters - Joko Setiono; Taufiq Rochman (Asian Journal Science and Engineering, 2022)
Green building aims to reduce environmental effect by improving indoor air quality for households and the community. Green buildings use the Greenship Rating Tools evaluation standards to accomplish environmentally sustainable residential development. Purpose of the study: The most important part of this thesis is to do a engineering and financial preliminary study before the construction of houses. Methods: Three home types (48/66, 70/84, and 80/112) will be used to generate Malang Residential Home data for this project. On the basis of BBC, BFC, and GBC, the technical viability will be assessed. The NPV, BCR, IRR, and PBP will be utilized to establish the project's financial viability. Variations in capital proportion, as well as increases or decreases in project revenue and outcome, would all be included when calculating sensitivity. Results: Between 60% and 75% of the BBC's technical feasibility has been determined, whereas BFC is between 0.60 and 1%, and GBC is larger than 10%. To put Malang Residential Housing in the silver level, IDR 1,382,745,228 was the NPV, with a BCR of 1.02, an IRR of 59.75 percent, and a PBP of one year and six months. It was concluded that the project was viable based on the sensitivity of the project's income and results to its viability. Keywords: Greenship Rating Tool, Engineering Feasibility, Financial Preliminary Study